A weekend with Winslow Homer - Beneduce, Ann. (New York : Rizzoli, 1993)
American painter Winslow Homer talks about his life and work as if entertaining the reader for the weekend. Includes reproductions of the artist's works and a list of museums where they are on display.
Junior High School Library Catalog (Wilson)
School Library Journal
Booklist
6.9
3-6
Keywords: Homer, Winslow, -- 1836-1910 -- Juvenile literature; Homer, Winslow, -- 1836-1910.; Homer, Winslow, -- 1836-1910.; Artists -- United States -- Biography -- Juvenile literature; Artists; American artists -- Biography